Identification of short open reading frames in plant genomes - Feng, Yong; Jiang, Mengyun; Yu, Weichang; Zhou, Jiannan (Frontiers in Plant Science, 2023)
The roles of short/small open reading frames (sORFs) have been increasingly recognized in recent years due to the rapid growing number of sORFs identified in various organisms owing to the development and application of Ribo-Seq technique, which sequences the ribosome-protected footprints (RPFs) of the translating mRNAs. However, special attention should be given when RPFs are used to identify sORFs in plants due to their small size ( 30 nt) and the high complexity and repetitiveness of the plant genome, particularly for polyploidy species. In this work, we compared different approaches in the identification of plant sORFs, discussed the advantages and disadvantages of each method, and provided a guide for the choosing of different methods in plant sORF studies.